pull down to refresh

This is as far as I got. Maybe someone else can take it the rest of the way
u = x^4
du = 4x^3 dx
\int_{0}^{1} \frac{4x^3 \left(1+x^{4(2006)}\right)}{(1+x^4)^{2008}} dx = \int_{0}^{1} \frac{1+u^{2006}}{(1+u)^{2008}} du
= \int_{0}^{1} \frac{1}{(1+u)^{2008}} du + \int_{0}^{1} \frac{u^{2006}}{(1+u)^{2008}} du
The left term can be easily calculated.
For the right term, let
F(k) = \int_{0}^{1} \frac{u^{k}}{(1+u)^{k+2}} du 
Using integration by parts, you can show that:
F(k) = \left. -\frac{u^{k}}{(k+1)(1+u)^{k+1}} \right|_{0}^{1} + \frac{k}{k+1} F(k-1)
Starting at F(0) which is easy to calculate, you can use the above algorithm to eventually calculate F(2006) to find the answer.
For the right term, one can do another substitution. Will write it out later.
reply